Modeling of simple AC traction drive using MATLAB/Simulink / Saiful Azhar Abdull Manaf - Abdull Manaf, Saiful Azhar (2007)
This paper presents a simulation study of performance characteristics of a simple AC traction drive using simulation model developed based on MATLAB/Simulink software. The availability of this developed simulation model enables the operational behavior of the performance parameters to be determined and analyzed. The understanding of these performance characteristics behaviors, particularly its dynamic characteristics are significantly important for design analysis. It provides vital information for selecting of precise design specifications and accurate prediction of performance characteristics of the developed drives system when operating over wide variation of load and speed characteristics. This subsequently will lead to the better understanding of operating the drives system at high optimum operating efficiency.